Inefficiencies and vulnerabilities of telephone-based communication between U. S. poison control centers and emergency departments. (June 2013) - Cummins, Mollie R.; Crouch, Barbara; Gesteland, Per; Wyckoff, Anastasia; Allen, Todd; Muthukutty, Anusha; Palmer, Robin; Peelay, Jitsupa; Repko, Katherine
<x xml:space="preserve">Abstract</x> Context. Poison control centers (PCCs) and emergency departments (EDs) rely upon telephone communication to collaborate. PCCs and EDs each create electronic records for the same patient during the course of collaboration, but those electronic records are not shared. Objective. The purpose of this study was to describe the current, telephone based process of PCC–ED communication as the basis for potential process improvement. Materials and methods. This study was conducted at one PCC and two tertiary care EDs. We developed workflow diagrams to depict clinician descriptions of the current process, descriptions obtained through interviews of key informants. We also analyzed transcripts of phone calls between emergency departments and the poison control center, corresponding to a random sample of 120 PCC cases occurring January 1–December 31, 2011. Results. Collaboration between the ED and PCC takes place during multiple telephone calls, and the process is unsupported by shared documentation. The process occurs in three phases: notification, collaborative care, and ongoing consultation. In the ED, multiple care providers may communicate with the PCC, but only one ED care provider communicates with the poison control center specialist at a time. Handoffs occur for both ED and PCC. Collaborative care planning is common and most cases involve some type of request for information, whether vital signs, laboratory results, or verification that a treatment was administered. We found evidence of inefficiencies and safety vulnerabilities, including the inability of PCC specialists to reach ED care providers, telephone calls routed through multiple ED staff members in an attempt to reach the appropriate care provider, and exchange of clinical information with non-clinical staff. In 55% of cases, the patient was discharged prior to any synchronous telephone communication between the ED care provider and a PCC specialist. Ambiguous communication of information was observed in 22% of cases. In 12% of cases, a PCC specialist was unable to obtain requested information from the ED. Discussion and conclusion. Inefficiencies and vulnerabilities occur in telephone-based PCC–ED communication. Prudence begs consideration of alternative processes and models of ED–PCC communication and information sharing, including a process that supports collaboration with health information exchange.